Isolation and characterization of dengue virus serotype 2 from the large dengue outbreak in Guangdong, China in 2014 - Zhao, Hui (Sci China Life Sci, 2014)
Dengue has been well recognized as a global public health threat, but only sporadic epidemics and imported cases were reported in recent decades in China. Since July 2014, an unexpected large dengue outbreak has occurred in Guangdong province, China, resulting in more than 40000 patients including six deaths. To clarify and characterize the causative agent of this outbreak, the acute phase serum from a patient diagnosed with severe dengue was subjected to virus isolation and high-throughput sequencing (HTS). Traditional real-time RT-PCR and HTS with Ion Torrent PGM detected the presence of dengue virus serotype 2 (DENV-2). A clinical DENV-2 isolate GZ05/2014 was obtained by culturing the patient serum in mosquito C6/36 cells. The complete genome of GZ05/2014 was determined and deposited in GenBank under the access number KP012546. Phylogenetic analysis based on the complete envelope gene showed that the newly DENV-2 isolate belonged to Cosmopolitan genotype and clustered closely with other Guangdong strains isolated in the past decade. No amino acid mutations that are obviously known to increase virulence or replication were identified throughout the genome of GZ05/2014. The high homology of Guangdong DENV-2 strains indicated the possibility of establishment of local DENV-2 circulation in Guangdong, China. These results help clarify the origin of this epidemic and predict the future status of dengue in China. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s11427-014-4782-3 and is accessible for authorized users.